Penyelesaian Konflik dengan Mediasi dan Rekonsiliasi dalam Kehidupan Transmigran Jawa melalui Sanksi Adat Masyarakat Islam di Tanah Gayo: Studi Kasus Masyarakat Desa Paya Tungel Kecamatan Jagong Jeget - Niswah, Sayyidatin; Ritonga, Sakti; Desky, Ahmed Fernanda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research discusses conflict resolution in the lives of Javanese transmigrants in the Paya Tungel Village, Jagong Jeget district, through the mediation of the Jagong Jeget district, which depends on the customary law applied by the indigenous population in Gayo land. In the customary law of the Islamic community in Jagong Jeget, conflict resolution involves the role of Tuha Peut (Village Government). A descriptive qualitative research method was used to obtain in-depth explanations through four informants who are Tuha Peut (Village Government) in Paya Tungel Village. The results show that conflict resolution in Paya Tungel uses mediation, reconciliation, and sanctions/laws to deter perpetrators, as well as guidance by Tuha Peut (Village Government) if the problem cannot be resolved within the family. Ralf Dahrendorf suggests mediation and reconciliation methods in resolving conflicts, as well as through compromise (Consensus) by recognizing differences in interests and seeking common ground acceptable to all parties involved.